Analysis of Air Quality Problems in the Engine Room Using the USG method - Kadek Ceisa Ari Putri Laksmi; Agus Prawoto; Dyah Ratnaningsih; Antonius Edy Kristiyono; Intan Sianturi (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2026)
Air quality in a ship's engine room significantly impacts crew health and operational safety, yet the priority of the problem remains underexplored in the Indonesian maritime context. This study analyzes air quality issues in the engine room of KM Sabuk Nusantara 101 using the USG (Urgency, Seriousness, Growth) method. With a quantitative cross-sectional survey design, data were collected through a Likert-scale questionnaire from a purposive sample of 30 engineers (Chief to 4th Engineer) with at least one year of experience in the engine room. The instrument was validated (r_hitung > 0.374) and reliable (Cronbach's α > 0.80) using SPSS. The analysis included descriptive statistics and calculation of USG scores for problem ranking. The results showed gas leaks as the top priority (USG score 13.66), followed by bilge odor (11.56) and increased temperature (11.34). In conclusion, routine seal repair, daily bilge cleaning, and blower optimization are recommended to reduce USG scores by up to 20 percent, improving crew safety and compliance with IMO 2020 regulations.